Rethinking real-time strategy games for virtual reality - Truman, Samuel; Rapp, Nicolas; Roth, Daniel; Von Mammen, Sebastian (ACM International Conference Proceeding Series, 2018)
Recent improvements in virtual reality (VR) technology promise the opportunity to redesign established game genres, such as real-time strategy (RTS) games. In this work we have a look at a taxonomy of RTS games and apply it to RTS titles for VR. Hereby, we identify possible difficulties such as the need for novel means of navigation in VR. We discuss conceivable solutions and illustrate them by referring to relevant work by others and by means of AStar0ID, an exploratory prototype VR RTS science fiction game. Our main contribution is the systematic inspection and discussion of foundational RTS aspects in the context of VR and, thus, to provide a substantial basis to further rethink and evolve the RTS genre in this new light.
CRIS-Team Scopus Importer:2021-03-29